The prince and the pauper - Davidson, Susanna (London: Usborne, 2008)
In Tudor England, a young ragged boy wanders the streets to beg for money. He passes the golden gates of Westminster Palace and there, by chance, he meets the prince. It is a moment that will change both their lives, forever ..
Keywords: Children's stories